1972
DOI: 10.1121/1.1912993
|View full text |Cite
|
Sign up to set email alerts
|

Research on Fan Noise Generation

Abstract: Different aspects of multiple-pure-tone (MPT) "broadband" noise generation in high-speed fans are discussed. An analytical model for multiple-pure-tone generation is presented. Experimental evidence indicates that the MPT generation does not seem to be a function of the presence of shock waves. It is also shown that fan "broadband" noise is not broadband in character and could be attributed to the modulation of the blade-passing-frequency tones, their sub-and higher harmonics. INTRODUCTIONThe subject of fan no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…(3) and (4), the resulting equations become identical to the Statistically Optimal Nearfield Acoustical Holography (SONAH) description as Hald presented in Ref. 11.…”
Section: Generalized Planar Nah Theorymentioning
confidence: 86%
See 1 more Smart Citation
“…(3) and (4), the resulting equations become identical to the Statistically Optimal Nearfield Acoustical Holography (SONAH) description as Hald presented in Ref. 11.…”
Section: Generalized Planar Nah Theorymentioning
confidence: 86%
“…These noise components are usually present below the Blade Passing Frequency (BPF) defined as the multiplication of the rotation frequency and the number of blades. Benzakein observed that these noise components are generated at the fan leading edges in the form of shock waves and propagate only at supersonic blade tip speeds 3 . In landing conditions where the blade tip speed is subsonic, the fan noise mainly consists of the BPF and its harmonic components as well as broadband frequency components.…”
Section: Introductionmentioning
confidence: 99%